The benefit of chitosan adding as a reinforcement material for polymethyl methacrylate provisional fixed dentures - Aidilla, Dara; Chairunnisa, Ricca; Syafrinani (Indonesian Journal of Prosthodontic, 2024)
Backgrounds: Provisional fixed partial denture (FPD) is an important procedure in prosthetic treatment such as crown or bridge. In particular cases, like crown lengthening as preliminary treatment, implant procedure until osseointegration process, and temporomandibular disorder as an occlusal therapy, the use of provisional FPD will take 3-6 months until the insertion of definitive restoration. Therefore, materials used in making a provisional FPD should be able to preserve the prepared tooth, maintain the periodontal conditions, and have superior esthetic for a long time. Self-cure polymethyl methacrylate (PMMA) is a most commonly used material due to its biocompatibility, high wear resistance, ease of application, and superior esthetic. Nonetheless, unmodified self-curing PMMA has weaknesses due to its degradation process in the oral cavity, which affects its mechanical and physical properties. To overcome this, addition of reinforcement material, namely chitosan, in provisional FPD is necessary. Chitosan is polymer compound obtain through partial deacetylation of acetyl glucosamine through deacetylation of chitin base and modified into magnetic nanoparticles with size 100-400 nm to increase absorption power. The addition of nanotechnology to polymeric materials has shown significant appeal and improved mechanical and physical properties. Objectives: This review aims to explain the use of chitosan material in addition to self-cure PMMA provisional FPD to improve its mechanical and physical properties. Conclusion: Chitosan material can be an alternative option to improve the mechanical and physical properties of self-cure PMMA. Keywords: provisional fixed partial denture, self-cure PMMA, chitosan